Evaluating passive immunity in piglets from sows vaccinated with a PEDV S protein subunit vaccine - Jiajia Liu; Jiajia Liu; Guangli Hu; Shengjin Liu; Guangcai Ren; Liguo Gao; Liguo Gao; Zhiqing Zhao; Rui Geng; Dingli Wang; Xiao Shen; Feng Chen; et al. (Frontiers in Cellular and Infection Microbiology)
Porcine epidemic diarrhea virus (PEDV) is a highly contagious virus that causes severe diarrhea and high mortality in neonatal piglets. Current control measures, such as inactivated and live-attenuated vaccines, have limitations in providing complete protection. In this study, we evaluate the immunogenicity and protective efficacy of a PEDV S protein subunit vaccine compared to a traditional inactivated vaccine. Piglets and Sows were immunized with either the subunit vaccine or an inactivated vaccine, and serum samples were collected to assess IgG and neutralizing antibody levels. Results demonstrated that the S protein subunit vaccine induced significantly higher IgG and neutralizing antibody levels in both piglets and sows compared to the inactivated vaccine. Piglets born to immunized sows were challenged with a virulent PEDV strain. Piglets from the subunit vaccine group exhibited lower viral shedding, reduced clinical symptoms, and minimal intestinal lesions. These findings suggest that the PEDV S protein subunit vaccine provides enhanced immunity and protection against PEDV, making it a promising candidate for preventing PEDV infections in swine.